2015
DOI: 10.1115/1.4031447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freestream Turbulence on Deposition for Nozzle Guide Vanes

Abstract: An evaluation of the effect of freestream turbulence intensity on the rate of deposit accumulation for nozzle guide vanes (NGVs) was performed using the turbine reacting flow rig (TuRFR) accelerated deposition facility. The TuRFR allowed flows up to 1350 K at inlet Mach numbers of 0.1 to be seeded with coal fly ash particulate in order to rapidly evaluate deposit formation on CFM56 NGVs. Hot film and particle image velocimetry (PIV) measurements were taken to assess the freestream turbulence with and without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…(11) and (16), respectively. Experimental data from a recent study by Whitaker et al [24] are used for this purpose. Germane parameters are collected in Table 6.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…(11) and (16), respectively. Experimental data from a recent study by Whitaker et al [24] are used for this purpose. Germane parameters are collected in Table 6.…”
Section: Validationmentioning
confidence: 99%
“…Experimental values of accumulation factor taken from Ref [24]. compared with the predicted values of interaction probability at the given condition.…”
mentioning
confidence: 99%
“…For comparison of the capture efficiencies on the NGV, some results were obtained by considering various influence factors, such as particle material [24], particle size [25,29,34], gas temperature [25,34], blowing ratio [33], inlet turbulence level [37], deposition time [34], and hot streak [35,38,39]. Effects of the gas temperature and particle size are analyzed in fig.…”
Section: Testing Facility For Accelerated Depositionmentioning
confidence: 99%
“…The vanes are numbered 1-4, and the two center vanes are used to provide periodic flow conditions. In addition, Whitaker et al [37] designed a turbulence grid placed in the flow path upstream the NGV as shown in part D of fig. 1.…”
mentioning
confidence: 99%
“…The largest amount of deposition occurred on the leading edge. Whitaker et al [16] noted that the mass of deposition on the blade surface was dependent on particle size distribution, indicating that microparticles with larger sizes were easier to deposit on the surface. They concluded that a reduction of inflow turbulence intensity could slow down the deposition buildup and extend the service life of the turbine.…”
Section: Introductionmentioning
confidence: 99%